2010
DOI: 10.1021/ac101227a
|View full text |Cite
|
Sign up to set email alerts
|

Interplay of Permanent Charge and Hydrophobicity in the Electrospray Ionization of Glycans

Abstract: The analysis of N-linked glycans by mass spectrometry (MS) has been characterized by low signal-to-noise ratios and high limits of detection due to their hydrophilicity and lack of basic sites able to be protonated. As a result, every step in glycan sample preparation must be thoroughly optimized in order to minimize sample loss, contamination, and analytical variability. Importantly, properties of glycans and their derivatized counterparts must be thoroughly studied in order to exploit certain characteristics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
76
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(77 citation statements)
references
References 55 publications
1
76
0
Order By: Relevance
“…Additionally, even though permethylation has been shown to increase the glycan abundance but are not useful with larger glycans due to incomplete reaction dispersing the glycan signal across several different m/z channels. 18 LattovĂĄ et al have reported an efficient method for N-glycan analysis which involved one-step organic extraction in prior to Peptide-N-Glycosidase F (PNGase F) deglycosylation.…”
Section: 14mentioning
confidence: 99%
“…Additionally, even though permethylation has been shown to increase the glycan abundance but are not useful with larger glycans due to incomplete reaction dispersing the glycan signal across several different m/z channels. 18 LattovĂĄ et al have reported an efficient method for N-glycan analysis which involved one-step organic extraction in prior to Peptide-N-Glycosidase F (PNGase F) deglycosylation.…”
Section: 14mentioning
confidence: 99%
“…Muddiman' group further systematically discussed the interplay of permanent charge and hydrophobicity in ionization of glycan. The results demonstrated that the introduction of hydrophobic tags could increase the ESI response of glycans, while introduction of a permanent charge rendered the labeled glycans more solvated in electrospray droplet, resulting in a decrease in ESI response [47] . Therefore, several of neutral, hydrophobic tags, including 2-phenylacetohydrazide (GPN), 3-phenylpropanehydrazide (GPN2), 4-phenylbutanehydrazide (GPN3), 5-phenylpentanehydrazide (GPN4) and 4-phenethylbenzohydrazide (phenyl2-GPN), were further synthesized, of which phenyl2-GPN derivatization obviously increased the ionization of glycan.…”
Section: Derivatization Of Glycan/glycopeptidementioning
confidence: 98%
“…[14] Most aromatic compounds are good candidates for tagging saccharides because such derivatives not only increase hydrophobicity but also are easily detected by their optical properties (e.g. UV absorptions and fluorescence emission) during chromatography or electrophoresis.…”
Section: Derivatization Of Saccharides With Aromatic and Aliphatic Ammentioning
confidence: 99%